Antibacterial Properties of Biofilm Schiff Base Derived from Dialdehyde Cellulose and Chitosan - Agung Pratama; Firman Sebayang; Rumondang Bulan Nasution (Indonesian Journal of Chemistry, 2019)
Cellulose and chitosan are natural polymers that have been used as biocomposite. The aim of this research is to obtain biofilms from chitosan and oxidized cellulose crosslinks. This research is divided into three steps, i.e., isolation of cellulose from oil palm trunk and oxidation of cellulose using NaIO4 (0.2; 0.4; 0.6; 0.8; 1.0 mg/mL) to obtain dialdehyde cellulose (DAC), crosslink of oxidized cellulose with chitosan (DD = 72.85%) to obtain biofilm of chitosan/DAC (CDAC), and characterization of biofilms. The crosslinked reaction was confirmed by FT-IR analysis that showed the spectrum of Schiff base C=N group at 1651 cm–1. Tensile strength increased gradually when the NaIO4 concentration used was 0.2–0.6 mg/mL, but after those concentrations, the tensile strength slightly decreased. The morphology analysis showed that CDAC had smoother morphology than DAC, which was shown rough and showed some particle indicated the presence of unreacted cellulose. CDAC biofilms that prepared with 1.0 mg/mL NaIO4 showed the greatest antibacterial activity.